Faktor-Faktor yang Mempengaruhi Motivasi dan Keaktifan Belajar Siswa Mata Pelajaran Agama Buddha di SMPN 2 Mempawah Hilir - Apung Apung; Irawati Irawati (STAB Maitreyawira, 2025)
This research is based on the problems that occur in the factors that influence the motivation and students’ learning activeness in Buddhist subject at Junior High School 2 Mempawah Hilir, such as (1) Factors that influence students’ learning motivation in Buddhist subject, (2) Factors that influence students’ learning activeness in Buddhist subject. This study aims to describe factors that influence the motivation and learning activeness of students in Buddhist subject. This research is using a qualitative descriptive method. The data of this research was collected by doing an interview and observation. The interview was conducted by the principal, vice principal for curriculum affairs, vice principal for student affairs, parents and the ninth grade of Buddhism students. The observation was conducted directly and indirectly on the object of the research by filling out sheet. Based on the research conducted, it can be concluded that there are four things that influence motivation and students’ learning activeness. First, motivation is a factor that allows students to be more concentrated, more enthusiastic and creates feelings of joy so that students do not get bored easily, do not easily forget in their efforts to study. Second, learning activeness is influenced by physiological factor which include physical (sensory) and physical conditions, and psychological factor which include attention, response, and memory. While the physical condition becomes an inhibiting factor that influence students’ learning activeness. Meanwhile, the external factors that influence students’ learning activeness are non-social factors, such as places and facilities, then the social factors, such as teachers and friends. Places, facilities, and teachers are factors that support students’ learning activeness. Meanwhile, friends is a factor that influence students and lead them into a positive direction.